First report of Besnoitia besnoiti seropositive cattle in Greece - PAPADOPOULOS (Η. ΠΑΠΑΔΟΠΟΥΛΟΣ), E.; ARSENOS (Γ. ΑΡΣΕΝΟΣ), G.; PTOCHOS (Σ. ΠΤΩΧΟΣ), S.; KATSOULOS (Π. ΚΑΤΣΟΥΛΟΣ), P.; OIKONOMOU (Γ. ΟΙΚΟΝΟΜΟΥ), G.; KARATZIA (Μ.Α. ΚΑΡΑΤΖΙΑ), M. A.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ), H. (Journal of the Hellenic Veterinary Medical Society, 2017)
Aim of this study was to investigate presence of Besnoitia besnoiti infection in indigenous and imported cattle in Greece. A total of 450 bovine blood sera samples from 15 dairy herds of Northern Greece were tested using a commercially available kit to detect specific anti-B. besnoiti antibodies. Ninety-eight cows were found to be seropositive to B. besnoiti (22%). Seropositivity varied among herds from 0% to 35%. Results were analysed using a univariate analysis of variance. A full factorial model was developed, using as independent variables area of sampling (Thrace, Macedonia) and origin of cattle (local, imported). No significant effect was found of the variables included into the model (P > 0.05). It is concluded that seropositive dairy cows are present in Northern Greece; however, impact of this parasite on animal production in Greece remains a key topic for further investigation.